The Profile of Land Carrying Capacity and Food Security in Gunungkidul Regency, Yogyakarta - Sendiawati Iguna; Sudrajat Sudrajat; Rika Harini (Media Komunikasi Geografi, 2022)
The relationship between the problem of land carrying capacity and food security in Gunungkidul Regency has not been widely studied and has the potential to become an important problem in the field of social agriculture in the coming years. This study determined the level of carrying capacity of rice and corn production land and the food security level in Gunungkidul Regency, Special Region of Yogyakarta Province. Administratively, this research consists of 18 districts. The research data used in the form of secondary data from the Central Statistics Agency, the Department of Agriculture, Bappeda and the Department of Health in the 2020 publication year. Analysis of land carrying capacity profiles and food security by quantitative descriptive. The results showed that the value of the carrying capacity of land based on the production of rice, corn, soybeans, and cassava in Gunungkidul Regency showed that it was in class II where the sub-districts in Gunungkidul Regency were quite optimal in the carrying capacity of the land and were able to meet the demand for the food. The value of food security in each sub-district in Gunungkidul is different based on aspects of food availability, access and use of food. Gunungkidul Regency shows the results of food security in priority category 4. This means that the sub-districts in Gunungkidul Regency are already quite resilient in terms of food security. There is a need for intensification of agricultural land, diversification of food consumption and priority infrastructure as well as strengthening of social support to improve regional food security in Gunungkidul Regency.